2023
DOI: 10.3390/su151612394
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development Goals from Theory to Practice Using Spatial Data Infrastructure: A Case Study of UAEU Undergraduate Students

Khaula Alkaabi,
Kashif Mehmood,
Parama Bhatacharyya
et al.

Abstract: The importance of Education for Sustainable Development (ESD) in influencing students’ understanding of and behavior toward sustainability cannot be overstated. However, prior studies have shown that students generally lack comprehension of how to apply geography instruction in relation to territories and their contribution to the Sustainable Development Goals (SDGs). Although the relationship between the SDGs and academic institutions has been the subject of numerous research, it is still unknown how much kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
(76 reference statements)
0
0
0
Order By: Relevance
“…The study found that awareness of organic food is essential for farmers in terms of creating a greater market share. Alkaabi et al [18] explored Spatial Data Infrastructure (SDI) and quality education as tools to raise awareness levels among UAE University students. The authors developed, validated, and analyzed an SDI-based questionnaire to geography and non-geography cohorts to assess their knowledge of the SDGs.…”
Section: Related Workmentioning
confidence: 99%
“…The study found that awareness of organic food is essential for farmers in terms of creating a greater market share. Alkaabi et al [18] explored Spatial Data Infrastructure (SDI) and quality education as tools to raise awareness levels among UAE University students. The authors developed, validated, and analyzed an SDI-based questionnaire to geography and non-geography cohorts to assess their knowledge of the SDGs.…”
Section: Related Workmentioning
confidence: 99%